The determinant of healthcare childbirth among young people in Indonesia - Agung Dwi Laksono; Ratna Dwi Wulandari; Rukmini Rukmini (SAGE Publishing, 2021)
Background: Young people is a vulnerable period of the emergence of various problems that may occur especially to those who are pregnant. The study was aimed to analyze the determinants of healthcare childbirth among young people in Indonesia in 2017. Design and Methods: The samples of this study were young people (15-24 yo.) who labored in the last 5 years, and there were 3,235 female young people involved. The study analyzed some variables, such as childbirth healthcare, a type of residence, age, education, employment, marital, parity, wealth, insurance, the autonomy of family finances, the autonomy of health, knowledge of pregnancy danger signs, and ANC. The data were analyzed by binary logistic regression. Results: Young people in urban were 2.23 times more likely to attend healthcare childbirth than those in rural (95%CI 1.84-2.70). Young people who completed secondary education were 4.12 times more likely to undergo delivery care than no education (95% CI 1.51-11.23). The richest were 5.60 times more likely to experience delivery care than the poorest (95%CI 3.52-8.93). Health insurance gave 1.44 possibilities for undergoing labor and delivery care (95%CI 1.22-1.70). Besides, knowing the danger signs of pregnancy allowed 1.50 times the possibilities for them to access labor and delivery care (95%CI 1.27-1.78). Young people with ANC visits of ≥4 times had more 1.68 times possibilities for taking healthcare childbirth compared to those with that of <4 times (95%CI 1.38-2.06). Conclusions: The study concluded that the determinants of healthcare childbirth among female adolescents in Indonesia included a residence, education, wealth, insurance, knowledge of pregnancy danger signs, and ANC.